2004
DOI: 10.1086/423423
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Speeds of BIMA SONG Galaxies with Molecule‐dominated Interstellar Mediums Using the Tremaine‐Weinberg Method

Abstract: We apply the Tremaine-Weinberg method of pattern speed determination to data cubes of CO emission in six spiral galaxies from the BIMA SONG survey each with an ISM dominated by molecular gas. We compare derived pattern speeds with estimates based on other methods, usually involving the identification of a predicted behavior at one or more resonances of the pattern(s). In two cases (NGC 1068 and NGC 4736) we find evidence for a central bar pattern speed that is greater than that of the surrounding spiral and ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 88 publications
(150 reference statements)
12
74
0
Order By: Relevance
“…Chemin et al (2003) have assumed that the inner ring-like feature found by Regan et al (2002) but not by us, corresponds to the location of an ultra-harmonic resonance. Rand & Wallin (2004), using the BIMA SONG data and the TremaineWeinberg method, have measured a pattern speed of the bar of Ω p = 50 +3 −8 km s −1 kpc −1 , in good agreement with our determination.…”
Section: Dynamical Interpretationsupporting
confidence: 87%
“…Chemin et al (2003) have assumed that the inner ring-like feature found by Regan et al (2002) but not by us, corresponds to the location of an ultra-harmonic resonance. Rand & Wallin (2004), using the BIMA SONG data and the TremaineWeinberg method, have measured a pattern speed of the bar of Ω p = 50 +3 −8 km s −1 kpc −1 , in good agreement with our determination.…”
Section: Dynamical Interpretationsupporting
confidence: 87%
“…A similar effect has been observed in other Hα or CO observations (e.g., Rand & Wallin 2004;Hernandez et al 2005;Emsellem et al 2006). As a check for consistency with the stellar tracer, X values have been derived from the R-band image.…”
Section: The Bar Pattern Speedsupporting
confidence: 68%
“…However, there are many instances where that the results suggest otherwise. Results for NGC 3031 (W98), NGC 2915 (Bureau et al 1999), NGC 5194 (Zimmer et al 2004), NGC 1068 (Rand & Wallin 2004), NGC 4321 (Hernandez et al 2005), and NGC 6946 (Fathi et al 2007) show a decreasing trend for increasing |y|.…”
Section: The Original Solution Methods Of Tw84mentioning
confidence: 95%